The Food Stamp Program and Supplemental Security Income. - Trenkamp, Brad; Wiseman, Michael (Social Security Bulletin, 2007)
The Food Stamp Program (FSP) and Supplemental Security Income (SSI) are important parts of national public assistance policy, and there is considerable overlap in the populations that the programs serve. About half of all SSI recipients reside in FSP recipient households. This article uses Social Security administrative data and the Food Stamp Quality Control samples for federal fiscal years 2001-2006 to study the prevalence of food stamp receipt among households with SSI recipients, the contribution of FSP to household income, and the importance of various FSP features in contributing to the well-being of recipient households. The prevalence of FSP participation among households that include SSI recipients is estimated to have grown steadily over the entire 2001-2006 period, rising from 47.4 percent in 2001 to 55.6 percent in 2006. This growth has occurred across all age groups of SSI recipients. The FSP contribution to household income has grown as well. In 2001, FSP increased the income of the households of SSI/FSP recipients by 13 percent; by 2006 the increase was 16.8 percent. Almost 80 percent of the food stamp recipient households that include SSI recipients receive increased benefits because of excess housing costs. In 2006, 44 percent of SSI recipients lived in households that did not receive food stamps. Given available information, it is difficult to gauge the FSP eligibility of nonparticipating households and, therefore, to assess the potential benefit of outreach efforts. Currently available measures of FSP take-up probably overstate participation among eligible households that include SSI recipients, and there is some evidence that enhanced state promotion of the FSP raises participation among households with SSI recipients. We conclude with recommendation for review and renewal of collaboration between the Food and Nutrition Service of the U.S. Department of Agriculture (the agency responsible for administering the FSP) and the Social Security Administration in ensuring that eligible SSI recipients utilize FSP benefits.